From resource variation to habitat loss: how changing environment shapes the plant-pollinator interactions - Akter, Asma (Jihočeská univerzita, 2021)
Annotation: Akter, A. and Klecka, J. 2020. Interactive effects of temperature, water, and nitrogen availability on the growth, floral traits, and pollination of white mustard, Sinapis alba. This was an experimental approach where Sinapis alba (white mustard), an economically beneficial crop was grown under different environmental conditions. Here, we assess how different growing conditions affected the growth of S. alba and the impact of different climate changing drivers on pollination and seed production. Akter, A., Biella, P., Klecka, J. 2017. Effects of small-scale clustering of flowers on pollinator foraging behaviour and flower visitation rate. PLoS ONE 12(11): e0187976. In this part of research, we experimentally changed the spatial structure of flower in small patches and assessed the impact on the foraging behaviour of pollinators, particularly, A. mellifera. Akter, A., Biella, P., Klecka, J. 2020. Introduction of new floral resources into plant-pollinator communities: impact on flower visitation mediated by species traits. This field-based experiment showed the impact of experimentally introduced floral resources in a plant community and how the response of the pollinator communities towards the new resources were mediated by the floral traits. Biella, P., Akter, A., Pajares, A.J.M., Federici, G., Galimberti, A., Jersáková, J., Labra, M., Mangili, F., Tommasi N. and Mangili, L. 2020. Pollination strategies of a plant in an unstable habitat: the case of the narrow-endemic toadflax Linaria tonzigii (Plantaginaceae). In this field-based research we assessed the pollination and reproduction strategies of an endemic plant, Linaria tonzigii, and the relation between the genetic variation and distribution. Akter, A., Biella, P., Batáry, P., Klecka, J. 2020. Changing pollinator communities along a disturbance gradient in the Sundarbans mangrove forest: a case study on Acanthus ilicifolius and Avicennia officinalis. Global Ecology and Conservation 24: e01282. This study was carried out in the Sundarbans mangrove forest, where we assessed the impact of human disturbances and forest loss on the plant-pollinator communities.
From resource variation to habitat loss: how changing environment shapes the plant-pollinator interactions
Keywords: Plant-pollinator interactions; climate change; environmental impact; pollination; foraging behaviour; functional traits; plant reproductive strategies; resource variation; alien plant; plant reproduction; human disturbances; bees; tropical ecology; floral resources; plant-pollinator diversity; conservation.; Plant-pollinator interactions; climate change; environmental impact; pollination; foraging behaviour; functional traits; plant reproductive strategies; resource variation; alien plant; plant reproduction; human disturbances; bees; tropical ecology; floral resources; plant-pollinator diversity; conservation.